A retrospective study of the efficacy and safety of levofloxacin in children with severe infection - Junqi, Zhang; Jie, Cai; Jinglin, Wang; Jinmiao, Lu; Guoping, Lu; Yi, Wang; Zhiping, Li (Frontiers in Pediatrics, 2024)
Objectives Levofloxacin is widely used because of its broad-spectrum antimicrobial activity and convenient dosing schedule. However, the relevance of its use in children remains to be investigated. The purpose of this study is to investigate the efficacy and safety of levofloxacin use in children with severe infections. Methods We conducted a retrospective observational study of patients <18 years of age who received levofloxacin intravenously in the Pediatric Intensive Care Unit (PICU) of our hospital during the period between 2021 and 2022. Patient demographics, course characteristics, clinical effectiveness, and adverse event correlations were extracted through a retrospective tabular review. Results We included 25 patients treated with 28 courses of levofloxacin. The mean age of these children treated with levofloxacin was 4.41 years. Conversion of pathogenic microbiological test results to negative after levofloxacin treatment was detected in 11 courses (39.29%). A decrease in inflammatory markers, white blood cell or C-reactive protein counts, was detected in 18 courses (64.29%). A total of 57 adverse events occurred during the treatment period, of which 21 were possibly related to levofloxacin and no adverse events were probably related to levofloxacin. Conclusion The effectiveness of levofloxacin use in children with serious infections is promising, especially for the treatment of multidrug-resistant bacteria. Adverse events occurring during the initiation of levofloxacin therapy in children are reported to be relatively common, but in this study, only a small percentage of them were possibly related to levofloxacin, and none of them were highly possibly related to levofloxacin.